Environmental Enrichment Improves Cognitive Deficits, AD Hallmarks and Epigenetic Alterations Presented in 5xFAD Mouse Model - Griñán-Ferré, Christian; Izquierdo, Vanesa; Otero, Eduard; Puigoriol-Illamola, Dolors; Corpas, Rubén; Sanfeliu, Coral; Ortuño-Sahagún, Daniel; Pallàs, Mercè (Frontiers in Cellular Neuroscience, 2018)
Cumulative evidence shows that modifications in lifestyle factors constitute an effective strategy to modulate molecular events related to neurodegenerative diseases, confirming the relevant role of epigenetics. Accordingly, Environmental Enrichment (EE) represents an approach to ameliorate cognitive decline and neuroprotection in Alzheimer´s disease (AD). AD is characterized by specific neuropathological hallmarks, such as β-amyloid plaques and neurofibrillary tangles, which severely affect the areas of the brain responsible for learning and memory. We evaluated EE neuroprotective influence on 5xFAD mice. We found a better cognitive performance on EE versus Control (Ct) 5xFAD mice, until being similar to Wild-Type (Wt) mice group. Neurodegenerative markers as β-CTF and tau hyperphosphorylation, reduced protein levels whiles APPα, postsynaptic density 95 (PSD95) and synaptophysin (SYN) protein levels increased protein levels in the hippocampus of 5xFAD-EE mice group. Furthermore, a reduction in gene expression of Il-6, Gfap, Hmox1, and Aox1 was determined. However, no changes were found in the gene expression of neurotrophins, such as Bdnf, Ngf, Tgf, and Vgf in mice with EE. Specifically, we found a reduced DNA-methylation level (5-mC) and an increased hydroxymethylation level (5-hmC), as well as an increased histone H3 and H4 acetylation level. Likewise, we found changes in the hippocampal gene expression of some chromatin-modifying enzyme, such as Dnmt3a/b, Hdac1, and Tet2. Extensive molecular analysis revealed a correlation between neuronal function and changes in epigenetic marks after EE that explain the cognitive improvement in 5xFAD.